Situated knowledge and biodiversity: tensions between organic smallholders from Southern Brazil and the international intellectual property regime - Waterloo Radomsky, Guilherme Francisco (2013)
The article approaches knowledges and biodiversity maintenance among ecological farmers in the west of Santa Catarina state, Brazil. The intellectual property rights have had direct effects onseed production. Between patents and other systems of control, family farmers deny treating life as a «resource». This paper has adouble aim: firstly, to analyze the intellectual property international panorama over biodiversity and knowledge; secondly, to examine practices of organic smallholders engaged to Rede Ecovida de Agroecologia (an organic farming network born in the southern Brazil) related to alternative forms of knowledge management and production of patent-free seeds. The result is the action which parallels the critique of the decrease on the availability of crop varieties and the effort to multiply seeds and knowledges throughout networks and agro-biodiversity centres.